2018
DOI: 10.1002/oby.22329
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Eating Pace (RePace) Behavioral Intervention for Children Prone to or with Obesity: Does the Turtle Win the Race?

Abstract: Objective: Rapid eating is a risk factor for childhood obesity but has not been a focus of intervention with young children. The short-term effects of a novel family-based treatment, "Reduced Eating Pace" (RePace), were tested on child eating speed and secondary outcomes. Methods: Twenty-eight rapid eating children were randomized to RePace (n = 14) or Delayed Usual Care Control (DUC) (n = 14). RePace taught families a slower eating pace using psychoeducational and behavioral techniques, including silent vibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 36 publications
2
48
0
Order By: Relevance
“…This creates opportunities to design interventions that combine changes in dietary choices and eating behaviors to reduce the risk of excessive energy consumption. Previous intervention trials have shown clinically significant reductions in both energy intake and body weight through the use of programs focused on re-training an individual's eating rate [28][29][30]. There is widespread agreement that the availability of low-cost, energy dense foods that are consumed in large portions can promote passive energy overconsumption [31].…”
Section: Discussionmentioning
confidence: 99%
“…This creates opportunities to design interventions that combine changes in dietary choices and eating behaviors to reduce the risk of excessive energy consumption. Previous intervention trials have shown clinically significant reductions in both energy intake and body weight through the use of programs focused on re-training an individual's eating rate [28][29][30]. There is widespread agreement that the availability of low-cost, energy dense foods that are consumed in large portions can promote passive energy overconsumption [31].…”
Section: Discussionmentioning
confidence: 99%
“…Although not specifically related to the ability to regulate food intake, some investigators have referred to eating behaviors that make up meal microstructure (e.g., bite rate, eating rate, and bite size) as indicators of satiety responsiveness [91]. Of these characteristics, eating rate has been most consistently associated with weight status in adults [92] and children [93], and is therefore a target for interventions to treat obesity [94]. Observational coding of meal-time behaviors in the GUSTO cohort from Singapore showed that male children have faster eating rate (g/min), larger bite size (g/bite), and shorter oral exposure (min) than female children [95].…”
Section: Evidence For Sex Differences In Children’s Eating Behaviormentioning
confidence: 99%
“…A recent review appraised a number of commercial apps targeting appetite regulation [ 17 ]. Research-driven interventions include real-time technology-assisted tools for meal times, including utensils with vibrotactile feedback [ 12 , 14 ] and Mandolean, a plate scale measuring eating rate with real-time computer or smartphone feedback [ 13 , 15 , 16 ]. Mandolean has shown promise for the treatment of childhood obesity [ 16 ].…”
Section: Introductionmentioning
confidence: 99%